3D printing of graphene oxide composites with well controlled alignment. (January 2021) - Qian, Yue; Li, Cheng; Qi, Yuzhao; Zhong, Jing
Abstract: As a super-anisotropic material, graphene possesses unprecedented strength, Young's modulus and electrical/thermal conductivity in its plane direction, while extremely weak properties along perpendicular direction. In order to fully take the advantage of graphene, its alignment in 3D polymer based structure is extremely important, yet still a daunting task. Here, we report a universal strategy of aligning graphene oxide (GO) in large scale without any modification of GO. This approach consists of laminating GO nanosheets with polymer (polylactic acid (PLA) for the demonstration) thin film, scrolling and then 3D printed by filament fused deposition technique. In printed filament, GO nanosheets are aligned in the filament axial direction, based on which GO orientation can be easily controlled via the path of filament fused deposition. We show that PLA/GO scrolled fibers and printed fibers with graphene content of 0.4 wt% exhibit outstanding mechanical properties with strength increase about 32.7% and 35.2%, respectively, which is significantly higher than similar nanocomposites with random graphene distribution, indicating much improved polymer reinforcement efficiency. The proposed scrolled fiber with 3D printing framework could be broadly applicable for various 2D materials and structural composites. Graphical abstract: Image 1